2016
DOI: 10.1136/tobaccocontrol-2016-053060
|View full text |Cite
|
Sign up to set email alerts
|

How do consumers perceive differences in risk across nicotine products? A review of relative risk perceptions across smokeless tobacco, e-cigarettes, nicotine replacement therapy and combustible cigarettes

Abstract: The highly variable and context-specific nature of non-combustible nicotine product RRPs have direct implications for researchers and present several challenges for policymakers working with modified risk products, including issues of measurement, health risk communication and behaviour change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 82 publications
9
89
1
1
Order By: Relevance
“…Our starting point for the simulation analysis is a scenario which we believe to approximate the state of the world at the time our DCE was conducted (2015). We define the state of the world as follows: e‐cigarettes are considered to be healthier than tobacco cigarettes by 70% of adults (Czoli et al ), e‐cigarettes are considered to be an effective cessation device by 33% of adults (Tan, Lee, and Bigman ), use of e‐cigarettes in public places is allowed in most states, and there is no e‐cigarettes tax . To implement assumptions regarding health and effectiveness as cessation device, 70% and 33% of respondents in our sample were randomly assigned a value of one for the corresponding attribute .…”
Section: Simulationsmentioning
confidence: 99%
“…Our starting point for the simulation analysis is a scenario which we believe to approximate the state of the world at the time our DCE was conducted (2015). We define the state of the world as follows: e‐cigarettes are considered to be healthier than tobacco cigarettes by 70% of adults (Czoli et al ), e‐cigarettes are considered to be an effective cessation device by 33% of adults (Tan, Lee, and Bigman ), use of e‐cigarettes in public places is allowed in most states, and there is no e‐cigarettes tax . To implement assumptions regarding health and effectiveness as cessation device, 70% and 33% of respondents in our sample were randomly assigned a value of one for the corresponding attribute .…”
Section: Simulationsmentioning
confidence: 99%
“…In a review paper, Czoli et al 12 report that substantial proportions of respondents in 54 studies reported inaccurate beliefs about the relative harmfulness of smokeless tobacco versus combustible cigarettes. This has important ramifications given the history of ‘no safe tobacco product’ messages that have long been promoted by health authorities, particularly in the USA.…”
mentioning
confidence: 99%
“…Additionally, there is a need for health professionals to challenge black and white thinking around smoking and quitting that serves to support smoking behaviour. Even among those who appeared interested in quitting smoking, there was a tendency to overemphasize the negative health, financial, effectiveness and lifestyle elements of alternatives to smoking in their deliberations [33]. While an idealisation of becoming a healthful and thrifty non-smoker appears to be part of what motivates some participants to want to quit, it also works against those who may struggle to quit smoking without assistance and/or may not be able to quit nicotine.…”
Section: Discussionmentioning
confidence: 99%